Peranan Guru dalam Pendidikan Karakter - Triana, Titin (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2016)
Character education is a system of instilling character values including knowledge, awareness, and actions to implement these values to the Almighty God, ourselves, others, the environment, human and nationality to become perfect man. Character education is an effort that should involve all parties, the household and the family, the school and the school environment, the community at large. It is used to improve the quality of the implementation and education results leading to the achievement of character building and morals that are holistic, integrated and balanced. This can be integrated in the learning in each subject. Instructional material relating to norms or values on each subject needs to be developed explicitly associated with the daily context. Character education can build national awareness and encourage students’ innovation and creativity. Beside, the values that must be built within the next generation are honesty, hard works, respect, cooperation, tolerance and discipline. In addition, the development of learner’s potentials can create a faithful man and fear of God Almighty, noble, healthy, knowledgeable, skilled, creative, independent, and democratic and responsible citizens. The formulation of these objectives reflects the growing expectations of the various parties to the education as the social agent instrument of human resource development.